2015
DOI: 10.7771/1541-5015.1501
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Influences of Using Peer Evaluation in Problem-Based Learning in Medical Education

Abstract: This study investigates the ways in which medical students' achievement goal orientations (AGO) affect their perceptions of learning and actual learning from an online problem-based learning environment, Calibrated Peer Review tM . First, the tenability of a four-factor model (Elliot & McGregor, 2001) of AGO was tested with data collected from medical students (N = 137). Then, a structural regression model relating the factors of AGO to students' perceptions of grading fairness, judgments of learning, and scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Coming from another motivational perspective, Abercrombie, Parkes, and McCarty (2015), in this issue, examine how students' achievement goal orientations affect their perceived fairness of peer evaluation, perceived learning, and the accuracy of their assessment of self and peers' problem solutions. The researchers found that the more performanceoriented a student was, that is, the more the individual focused on demonstrating his or her performance in comparison with that of others, the more likely he or she would perceive peer assessment to be unfair, and the less accurate was this individual's actual assessment of self and peers' problem solutions.…”
Section: Learner Motivation: Antecedents Of Pblmentioning
confidence: 99%
“…Coming from another motivational perspective, Abercrombie, Parkes, and McCarty (2015), in this issue, examine how students' achievement goal orientations affect their perceived fairness of peer evaluation, perceived learning, and the accuracy of their assessment of self and peers' problem solutions. The researchers found that the more performanceoriented a student was, that is, the more the individual focused on demonstrating his or her performance in comparison with that of others, the more likely he or she would perceive peer assessment to be unfair, and the less accurate was this individual's actual assessment of self and peers' problem solutions.…”
Section: Learner Motivation: Antecedents Of Pblmentioning
confidence: 99%
“…26 It was designed to facilitate peer-graded writing assignments in large lecture courses and has been widely adopted by educators in a variety of disciplines including biology, chemistry, engineering, and medical education. 1 , 12 , 14 , 15 Faculty have used CPR to assess essay writing, 28 lab reports and design reports, 12 technical writing, 16 and course content. 17 We were early pioneers in the use of CPR to teach technical posters.…”
Section: Introductionmentioning
confidence: 99%